Why Has It Been So Difficult to Transform Evaluation Practices of Learning in the Educational Context? A Critical Essay on a Pedagogical Pathology Still to Be Treated - Mario Hernández-Nodarse (Revista Electronic@ Educare, 2016)
In this work, learning assessment is discussed, assuming educational precepts for their ethical, moral and educational value. The study aims to share some ideas and to critically reflect on the persistence of the traditional evaluation practices, a kind of pedagogical pathology that is recurrently and widely criticized by authors and specialists. Certain causes, consequences and possible solutions for an educational evaluation are analyzed. Underlying issues associated with the relationship between the practices and concepts that support them are evaluated. It is concluded that the change in education and mentality, needed in this regard, is crucial to transform practices; and this will be possible if policies, strategies, implementations and actions are reconsidered to allow better pedagogical training of administrative and teaching staff in order to achieve greater efficiency and a real educational effect.